Tomato water consumption in the greenhouse according to the number of stems - Ruelas-Islas, Jesús del Rosario; Rubiños-Panta, Juan Enrique; Peinado-Fuentes, Luis Alberto; Mendoza-Pérez, Cándido; Martínez-Ruiz, Antonio; Escobosa-García, Isabel (Revista Mexicana de Ciencias Agrícolas, 2022)
The low availability of water observed in the country’s dams and the overexploitation of underground aquifers make it urgent to generate strategies to optimize this resource. One strategy is the optimization of irrigation by calculating water needs for irrigation scheduling. The objective of this study was to analyze the relationship between crop evapotranspiration (ETc) and crop coefficient (Kc) in tomato cultivation as a function of the number of stems, for the supply of irrigation water based on a drainage lysimeter and an atmometer. The work was carried out under controlled conditions using tezontle as a substrate and a drip irrigation system. The experiment consisted of three treatments, one (T1), two (T2) and three (T3) stems per plant. The drainage lysimeter method was used to measure daily crop transpiration (ETc) and an atmometer was used to estimate reference evapotranspiration (ETo). The accumulated transpiration of the crop was 352, 389 and 434 mm for T1, T2 and T3 and a Kc of 1.06, 1.16 and 1.32 for the same treatments, respectively, as well as the irrigation requirement of 1.04, 1.14 and 1.29 L plant-1, both parameters determined in the stage of maximum water and nutrient demand. It is concluded that the daily measurements of transpiration in tomato with the drainage lysimeter allow to reliably calculate the water requirement of crops, in addition, the atmometer is an alternative to estimate the ETo for irrigation scheduling purposes in different crops.
Keywords: crop coefficient; leaf area index; irrigation requirement; protected agriculture